Infants requiring maintenance dialysis: outcomes of hemodialysis and peritoneal dialysis - Vidal, Enrico; Schaefer, Franz (American journal of kidney diseases, 2017)
Background: The impact of different dialysis modalities on clinical outcomes has not been explored in young infants with chronic kidney failure. Study Design: Cohort study. Setting & Participants:Data were extracted from the ESPN/ERA-EDTA Registry. This analysis included 1,063 infants 12 months or younger who initiated dialysis therapy in 1991 to 2013. Factor: Type of dialysis modality. Outcomes & Measurements: Differences between infants treated with peritoneal dialysis (PD) or hemodialysis (HD) in patient survival, technique survival, and access to kidney transplantation were examined using Cox regression analysis while adjusting for age at dialysis therapy initiation, sex, underlying kidney disease, and country of residence. Results: 917 infants initiated dialysis therapy on PD, and 146, on HD. Median age at dialysis therapy initiation was 4.5 (IQR, 0.7-7.9) months, and median body weight was 5.7 (IQR, 3.7-7.5) kg. Although the groups were homogeneous regarding age and sex, infants treated with PD more often had congenital anomalies of the kidney and urinary tract (CAKUT; 48% vs 27%), whereas those on HD therapy more frequently had metabolic disorders (12% vs 4%). Risk factors for death were younger age at dialysis therapy initiation (HR per each 1-month later initiation, 0.95; 95% CI, 0.90-0.97) and non-CAKUT cause of chronic kidney failure (HR, 1.49; 95% CI, 1.08-2.04). Mortality risk and likelihood of transplantation were equal in PD and HD patients, whereas HD patients had a higher risk for changing dialysis treatment (adjusted HR, 1.64; 95% CI, 1.17-2.31). Limitations: Inability to control for unmeasured confounders not included in the Registry database and missing data (ie, comorbid conditions). Low statistical power because of relatively small number of participants. Conclusions: Despite a widespread preconception that HD should be reserved for cases in which PD is not feasible, in Europe, we found 1 in 8 infants in need of maintenance dialysis to be initiated on HD therapy. Patient characteristics at dialysis therapy initiation, prospective survival, and time to transplantation were very similar for infants initiated on PD or HD therapy.